A terceira velocidade do direito penal: o direito penal do inimigo - Moraes, Alexandre Rocha Almeida de (2006)
This work aims to analyze the theory of the Enemy Criminal Law in the light of the conception and methodology of GÜNTHER JAKOBS. It is the most controversial Criminal Policy of current times, but has been gradually entwining itself with rules, jurisprudence and legislations based on the classic-illuminist model. In order to assess legitimacy of a Criminal Law of such nature, which legal scholars have called the third pace of Criminal Law , we initially pointed out some traces of the context of the post-industrial society and outlined the new criminal claims of the modern world, with a clear-cut intention to show that the complexity of the contemporary society has been, for a long time, imposing changes on the criminal dogmatics, even prior to the formalization of JAKOBS concept. Based on the acknowledged complexity of modern society, we presented NIKLAS LUHMANN s systems theory, which was JAKOBS point of departure for the theoretical construction of his Law of Normality The Citizen s Criminal Law . By praising the functional distinction of (Political, Economic, Legal etc.) systems, LUHMANN advocates that the function of Law would be that of consistently stabilizing standardized expectations. This would be precisely the primary function of the penalty advocated by JAKOBS systemic functionalism. Thus, through the presentation of the systemic functionalism s new paradigms, it is possible to understand the theory of punishment in the Citizen s Criminal Law , which JAKOBS calls positive general prevention . By analyzing the conceptions about the purpose of punishment and once we finally outlined an overview of the Criminal Law of Normality, whose primary function is that of reaffirmation of Law itself in such a way as to ensure the configuration of society, we formally present his theory of the Enemy Criminal Law , with an indication of origin, concept, meaning, philosophical construal, normative distinction between person and enemy and, above all, we outlined their major features, emphasizing the role of early relief in Criminal Law, the use of disproportionate punishments and the relativization of criminal and procedural warranties. We furthermore stressed how the theory arose in a first plane, as a criticism in response to the discovery of criminal legislations and policies that were already making use of such parameters and, in a second plane, how the criticism turned into something held by JAKOBS as inevitable, reinforced by terrorist attacks perpetrated throughout the world. Moreover, similar precedents or institutions have been contemplated, contextualizing old and recent criminal policies to cope with ordinary and organized crime, such as those of the movements Law & Order , Zero Tolerance and the theory of broken windows , the author s Criminal Law that advocated the level of risk to the detriment of the Criminal Law of fact based on liability, the criminological classification of the perpetrator as professional , customary and by tendency , in addition to the use of safety measures to criminally imputable and dangerous individuals. The criticisms to the German jurist s conception were presented from a number of standpoints from non-compliance with Constitutional Principles to the inconsistency with JAKOBS methodological support itself so that we could eventually face the hard task to review the legitimacy of a third-pace Criminal Law in Democratic States, as well as the risks of ignoring its existence with subtle suggestions of confronting the issue on a short and long-term basis